High stakes at Hoopfest : a Rex Begonia mystery - Bieker, Chris (Bieker, Chris. Rex Begonia mysteries, 2024)
"Hoopfest, the world's largest three-on-three basketball tournament transforms into a high-stakes game for Spokane's top detective Rex Begonia and his partner Ivy Lizei. Mayor Sammy Prosciutto's shot at becoming Governor is blocked when his campaign takes a nasty turn and our favorite sleuths get netted into solving a murder." -- Amazon.